The Effect of Environmental Regulations on Financial Performance in Tanzania: A survey of Manufacturing Companies Quoted on the Dar es Salaam Stock Exchange - Naila, Daniel Linus (International Journal of Economics and Financial Issues, 2012)
There has been environmental pollution across the globe. Environmental activists are condemning manufacturing companies of environmental pollution. This has led to the establishment of environmental regulations and standards by government authorities across the globe. In complying with environmental regulations companies have found themselves incurring additional cost when compared to those companies which do not comply. However, the effect of compliance to environmental regulations on the financial performance is not clear. This study explores the effects of environmental compliance on the financial performance for listed manufacturing companies in Tanzania. Five listed manufacturing companies were surveyed to obtain data used for the purpose of this study. Specifically, the study intended to establish: the relationship between environmental compliance and financial performance and the effect of environmental compliance on the financial performance. Regression analysis was done to establish the relationship between environmental compliance and financial performance. Findings suggest that there is no significant relationship between environmental compliance and financial performance among listed manufacturing firms in Tanzania. This study concludes that environmental compliance has no significant effect on the financial performance for listed manufacturing firms in Tanzania. Keywords: Environmental regulations; Financial performance; Dar es Salaam stock exchange JEL Classifications: G; Q5